FINANCIAL PERFORMANCE AND OUTREACH OF MICROFINANCE - Loan, Ph?m Ng?c T??ng; Huy, Nguy?n T?n (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
Microfinance is generally considered as a power tool for poverty alleviation. However, the development ofÂ microfinance leads to a concern about self-sufficiency of microfinance institutions (MFIs). MFIs are expectedÂ not only to serve the poor but also to become profitable; and therefore adapting more commercial practices.Â From the point of view, the commercialization trend of microfinance has raised a debate that whether theÂ focuses on financial objectives go against the original goal of reducing poverty. Using cross-sectional dataÂ of Indian MFIs in 2010 collected from the MIX, this dissertation aims to explain determinants of MFIsâÂ performance in terms of financial objectives and outreach to the poor. The paper also tries to address theÂ trade-off between financial success outcomes and poverty reduction purposes. The study reveals that noÂ evidences of this trade-off are found, indicating that it is possible to maintain greater outreach to the poorÂ in a financially viable way.